Sosialisasi Penggunaan Aplikasi Liveworksheets sebagai LKPD Interaktif Bagi Guru-guru SD Negeri 1 Tegalmunjul Purwakarta - Anisa Nurbayani; Elisya Rahmawati; Isma Inayah Nurfaujiah; Nita Dinda Putriyanti; Nur'afni Fitria Fajriati; Yosy Safira; Acep Ruswan (Universitas Pendidikan Indonesia Kampus Purwakarta, 2021)
The Covid-19 pandemic that occurred had an impact on various fields, one of which was education. Teachers must be more creative and innovative in managing learning activities during the pandemic. By carrying out this activity, it is hoped that it can inform and assist teachers in making LKPD during online learning. This activity aims to inform and at the same time provide training on how to use the Liveworksheets application as an interactive LKPD; with the introduction of this application, it is hoped that teachers can attract more students to take part in online learning. Activities carried out online via zoom application. The results of this activity can be seen from the questionnaire filled out by the teacher as a participant; the teacher feels helped and is interested in using the Liveworksheets application as an option for evaluation media during online learning.